2009
DOI: 10.1007/s00586-009-1044-3
|View full text |Cite
|
Sign up to set email alerts
|

No effect of traction in patients with low back pain: a single centre, single blind, randomized controlled trial of Intervertebral Differential Dynamics Therapy®

Abstract: Low back pain (LBP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Nevertheless, the results of the current study seem to support the conclusions of recent reviews 17,30,31) in which no uniform evidence of the efficacy of traction therapy as a treatment for LBP was reported 23) . A limitation of our study is the lack of follow-up concerning the effects for at least after 3 months.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, the results of the current study seem to support the conclusions of recent reviews 17,30,31) in which no uniform evidence of the efficacy of traction therapy as a treatment for LBP was reported 23) . A limitation of our study is the lack of follow-up concerning the effects for at least after 3 months.…”
Section: Discussionsupporting
confidence: 81%
“…For example, studies that have been reported that lacked a randomized comparison group 1,18) , had a retrospective design [19][20][21][22] , had sample that were small 19,20) , studied heterogeneous patient groups 31) or had authors who were commercially related to the evaluated therapy 20,21) . Moreover, there is still controversy within this particular field because various different traction techniques and corresponding protocols exists 23) .…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have shown potential benefits of traction on restoring disc disruption, and such distraction and relaxation cycles are theorized to promote disc health by increasing nutrient flow into the degenerated disc. 3437 The RCT on traction therapy by Schimmel et al 37 found no significant differences in any clinical outcomes between patients receiving traction therapy, according to the manufacturer’s protocol, and a sham group using non-therapeutic weights. 37 (Table 3)…”
Section: Resultsmentioning
confidence: 99%
“…Six clinical studies failed to detect significant differences between active and sham/placebo therapies. 3739,4547 Five studies (Peng et al 43 , Cao et al 40 , Pauza et al 44 , Oh et al 48 and Kapural et al 49 ) which investigated intradiscal methylene blue injection, steroid therapy, IDET, ramus communicans ablation and intradiscal biacuplasty all demonstrated significant differences in clinical outcomes favoring intervention over sham treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation